Association of platelet-to-lymphocyte ratio with sepsis based on MIMIC-IV database - Zhao, Hui; Wang , Kai; Li , Zhiheng; Mao , Lili; Miao , Jinli; Sun, Yan (Vojnosanitetski pregled, 2025)
Background/Aim. Sepsis is a potentially lethal condition that ranks among the most severe medical disorders globally and results in elevated mortality rates. The aim of this study was to examine the correlation between sepsis outcomes in patients and the platelet-to-lymphocyte ratio (PLR), including mortality and duration of intensive care unit (ICU) stay from admission, while considering relevant demographic and clinical factors. Methods. In this retrospective study, the Medical Information Mart for Intensive Care (MIMIC)-IV dataset information was used. Sepsis patients were de-identified, and their PLR values were calculated upon admission. Multivariate logistic regression models were used to assess the relationship between PLR and mortality, adjusting for confounding variables such as age, gender, comorbidities, and vital signs. Additionally, the association between PLR and the length of the ICU stay was analyzed using linear regression models. Results. This study included 4,624 sepsis patients. Higher PLR values were significantly correlated with decreased survival probabilities in the unadjusted model [Model 1 – odds ratio (OR): 0.890, 95% confidence interval (CI): 0.810–0.970, p < 0.001]. This association remained significant after adjusting for demographic factors (Model 2 – OR: 0.920, 95% CI: 0.850–0.995, p
Keywords: biomarkers; blood platelets; intensive care unit; lymphocytes; mortality; sepsis